STUDENTS’ PARTICIPATION IN QUALITY ASSUARANCE AT UNIVERSITY - Oksana Bulvinska; Lesya Chervona (Неперервна професійна освіта: теорія та практика, 2020)
The article highlights the problems associated with the concept of involving students in the formation, development and implementation of vital decisions in the field of higher education. It is emphasized that the relevance of student participation is that students are not only a stakeholder but also an equal partner in the processes of university governance and in the process of ensuring the quality of higher education. The article analyses different approaches to the concept of «student voice». The authors propose to consider this concept as a philosophical and managerial idea that students have their unique opinion on education and they should be able to make a real contribution to decision-making in higher education, influencing results, expressing their views, promoting their ideas and feeling the results of their influence. Different models and mechanisms of student voice are presented: representation of students in the governing bodies of the university; activities of students in leading groups of educational programs; survey of students, focus groups; cooperation with the students’ organization; regular informal discussions between students and faculty and university management. The article analyses the practical implementation of different models and mechanisms of student voice in European universities: University College London and University of Helsinki, and reviews the impact of student voice on educational practice in Ukrainian higher education institutions on the example of the National Technical University of Ukraine «Kyiv Polytechnic Institute named after Igor Sikorsky». It is concluded that in Ukrainian universities, compared to European ones, the concept of cooperation with students as full partners in every aspect of their education has not yet found practical implementation; forms of students’ influence more often relate to socio-cultural and sports areas, organization of leisure and entertainment.